Implementation of change management through organizational restructuring intervention as a development strategy for Akar Tani Cooperative - Guntur Arafa; Hermeindito Hermeindito; Eric Harianto; Azwar Rhamdhan (Jurnal Mantik, 2026)
A farmer cooperative, Akar Tani (KAT) in Bantaeng, South Sulawesi, experienced declining active membership (100 to 74) and reduced coffee output (12 to 8 tons/year), alongside governance problems that weakened members’ trust due to delayed payments and poor records. This study examines how change management was enacted through organizational restructuring and identifies the key barriers that shaped the change trajectory. Using a qualitative case study design, we interviewed 11 informants (cooperative administrators, members, and external mentors), complemented by observations and document review. Data were analyzed iteratively using Miles and Huberman’s approach supported by NVivo. The findings show that barriers were driven less by rejection of cooperative goals and more by uneven digital literacy, entrenched work habits, fragmented internal communication, and sensitivity around administrative–financial transparency. Restructuring actions aligned with Kotter’s change stages, particularly capacity-building through practice-based training, multi-channel communication, clearer role division and SOPs, and early visible improvements in payment orderliness and financial information. This study contributes by extending change-management evidence to sustainability-oriented farmer cooperatives where trust recovery and collective learning are central mechanisms of restructuring. The practical implication is that cooperatives should prioritize transparency as a trust foundation while adopting gradual hybrid digitalization matched to members’ readiness. This research is limited to a single cooperative and does not track long-term quantitative performance outcomes; future studies may compare multiple cooperatives and assess digital readiness trajectories over time